(3GdMejGJs - (3ESMGb Hf SdjeGf GdGSQGFjdj, CHh jYbhH,J (B320 (3g` s ((3jMi GdeWQR GdOeTbi s)
(3ChdgG (B:s
(3GdebGdI GdChdi ai eHGjfI GdMei hMOgG GdeHfi Ydi WHjYJgG hai CSHGHgG hYddgG s
(3BNQgG (B:s
(3hUdGJ GdMei GdLfHjI UYHI dMOI GdOe GdehdO dgG hbQHgG ef GdbdH Je GdcJGH s
(3jMJhi Ydi NeS ebGdGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs